THE ROLE OF TECHNOLOGY IN EFL CLASSROOM - Fahri Haswani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
In response to an appeal from Indonesia’s Ministry of Education and Culture to all universities and colleges to improve the quality of tertiary education toward regional and international standard, language institutions are making great efforts to further promote the foreign language learning process. In the last few years there have been dramatic changes in the ways that languages are taught by communicative approach and the introduction of technological tools. In recent years, the use of technological aids, especially those related to computers, has increasingly become a common feature of the classroom. There is no doubt that computer based instruction will occupy a more central role in the foreign language classroom in the future. Information technology has drawn the interest of teachers of English as a second or foreign language in non-English speaking countries. The technology integration into the curriculum is not a single concept which is generated from one single theory nor does it give full guidelines for the implementation in practical situation. This issue constitutes ideas from many different theories. This paper discusses the issue of technology contributions in EFL classroom. The question raised in this paper is how technology facilitates the attainment of course goals. The answer of the question will help English teachers to clarify the real problems of the initiative so that the innovation and possible changes can be aligned with the need of the students. However, this literature review only covers limited issues related with the role of technology in EFL classroom. Further discussion from other different points of view is still needed to create more complete description of conceptual foundation of the innovation.